Prognostic factors for poor outcomes in patients with severe COVID-19 treated with remdesivir plus dexamethasone in Taiwan - Yi-Hsuan Lai; Yi-Chih Lee; I-Ren Chen; Shih-Neng Lin; Yuh-Lih Chang; Chih-Chia Lu; Ping-Feng Wu; Yi-Tsung Lin (Journal of Microbiology, Immunology and Infection, 2023)
Background: Coronavirus disease-2019 (COVID-19) remains a global public health concern, and remdesivir plus dexamethasone combination therapy is suggested for patients with severe disease. However, the factors associated with poor outcomes in these patients remain unclear. We identified the factors associated with poor outcomes in Taiwanese patients with severe COVID-19 treated with remdesivir plus dexamethasone. Methods: Adults with severe COVID-19 (oxygen saturation <94% on room air or requiring supplemental oxygen) treated with remdesivir and dexamethasone were identified between 1 May and 31 July 2021. The main outcomes were 14-day non-recovery, 28-day mortality, and progression to respiratory failure requiring invasive mechanical ventilation or death in initially non-ventilated patients. The prognostic factors associated with poor outcomes were analyzed by multivariate logistic regression and Cox regression. Results: Of the 110 patients treated with remdesivir and dexamethasone, 57 (51.8%) recovered within 14 days and 6 (5.5%) died within 28 days. Of the 89 initially non-ventilated patients, 12 (13.5%) progressed to respiratory failure or death. Charlson Comorbidity Index, SOFA score, and admission to remdesivir treatment interval were associated with 14-day non-recovery. C-reactive protein level was associated with 28-day mortality. Pneumonia Severity Index and admission to remdesivir treatment interval were associated with progression to respiratory failure requiring invasive mechanical ventilation or death in initially non-ventilated patients. Conclusion: High disease severity on admission and delayed initiation of remdesivir therapy were associated with poor outcomes in COVID-19 patients treated with remdesivir and dexamethasone.